2011
DOI: 10.1001/jama.2011.1556
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization-Associated Disability

Abstract: In older patients, acute medical illness that requires hospitalization is a sentinel event that often precipitates disability. This results in the subsequent inability to live independently and complete basic activities of daily living (ADLs). This hospitalization-associated disability occurs in approximately one-third of patients older than 70 years of age and may be triggered even when the illness that necessitated the hospitalization is successfully treated. In this article, we describe risk factors and ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
408
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 718 publications
(426 citation statements)
references
References 74 publications
12
408
0
6
Order By: Relevance
“…In further study, we would use muscle strength and physical performance as the independent variables to determine the association between sarcopenia and OVF. Recent reports have mentioned that bed rest and low energy intake among inpatients may cause sarcopenia and hospitalization-associated disability [38]. However, the present study estimated muscle mass within 48 h of admission; thus, the effect of bed rest was limited.…”
Section: Discussionmentioning
confidence: 67%
“…In further study, we would use muscle strength and physical performance as the independent variables to determine the association between sarcopenia and OVF. Recent reports have mentioned that bed rest and low energy intake among inpatients may cause sarcopenia and hospitalization-associated disability [38]. However, the present study estimated muscle mass within 48 h of admission; thus, the effect of bed rest was limited.…”
Section: Discussionmentioning
confidence: 67%
“…Through the use of protocols, physiotherapists who are unfamiliar with working practices in other departments, can still deliver care as best as possible. Unfortunately, these protocols carry the risk that all therapists will deliver protocolised and therapist centred (one-size-fits-all) care instead of the currently favoured patient centred and personalised care [13,14], as demonstrated by the high number of expert therapists using protocols to guide their day-to-day practice therapy in our study. We specifically included expert physiotherapists in our survey population to distil best (physiotherapy) practice in LSF [13,14].…”
Section: Comparison To the Literaturementioning
confidence: 93%
“…Unfortunately, these protocols carry the risk that all therapists will deliver protocolised and therapist centred (one-size-fits-all) care instead of the currently favoured patient centred and personalised care [13,14], as demonstrated by the high number of expert therapists using protocols to guide their day-to-day practice therapy in our study. We specifically included expert physiotherapists in our survey population to distil best (physiotherapy) practice in LSF [13,14]. Interestingly, we found that factors essential for clinical reasoning (such as functional diagnosis) were often not evaluated, therapy was either never or always provided (regardless of the patient's need), and therapy was typically delivered on time-based principles (not goal-based).…”
Section: Comparison To the Literaturementioning
confidence: 93%
“…Further, when immobility exists, patients of all ages are at risk for immobility-related adverse outcomes, many of which are non-reimbursable, as indicated by the Centers for Medicare and Medicaid Services. 19,20 Hazards of immobility that affect all hospitalized patients may include ventilator associated pneumonia (VAP), atelectasis, delayed extubation, peristaltic impairment, wound infections, depression, social isolation, embolic conditions, urinary tract infection, extended or repeated lengths of stay, and avoidable or unavoidable pressure ulcers. 21 The inability to reposition patients adequately is a significant concern, especially among obese, disabled, critical care, trauma, neurologic, or orthopedic patients.…”
Section: Implications For Bariatric Nursesmentioning
confidence: 99%